A narrow-band ultra-bright green phosphor for LED-based applications. Issue 6 (23rd January 2020) - Dong, Quan; Yang, Jiaojie; Cui, Jun; Xu, Fanfan; Yang, Fengli; Peng, Jiaqing; Du, Fu; Ye, Xinyu; Yang, Shaohua
Abstract : A narrow-band ultra-bright green phosphor, Sr2 MgB2 O6 :Ce 3+, Tb 3+, shows high thermal stability and quantum efficiency for LED-based applications. Abstract : A novel Sr2 MgB2 O6 (SMBO) green-emitting phosphor co-doped with Ce 3+ –Tb 3+ was synthesized at 950 °C via solid-state reactions, and the ultra-narrow-band green emission of Tb 3+ was significantly enhanced almost 20 times via energy transfer from Ce 3+ to Tb 3+ . It was found to have a broad excitation band (250 to 400 nm), and the full width at half-maximum (FWHM) of the dominant green emission band around 544 nm was only about 10 nm. The electronic band gap of the SMBO matrix was calculated by density functional theory (DFT) to be 4.60 eV, and this was well verified by the diffuse reflection spectra results. Furthermore, the composition-optimized phosphor SMBO:0.05Ce 3+, 0.05Tb 3+ exhibits excellent thermal quenching resistance (75.3% intensity at 423 K) and relatively high external quantum efficiency (EQE = 48.92%). Finally, two white light-emitting diode (WLED) packages were fabricated via combining a 365 nm n-UV chip, the optimal sample and commercial blue and red phosphors to assess the application potential of the phosphors. The test results indicate that the obtained WLEDs-1 fabricated with K2 SiF6 :Mn 4+ has an outstanding color rendering index ( R a = 85.7) and Commission Internationale de L'Eclairage (CIE) coordinates (0.3242, 0.3334). Meanwhile, the color gamut can reach 87% of the National Television Standards Committee (NTSC) CIE 1931 color gamut. WLEDs-2 fabricated with red emitting CaAlSiN3 :Eu 2+ produced warm white light with color coordinates of (0.3792, 0.3810), a high color rendering index of 82.3, and a low correlated color temperature of 4065 K. These results reveal the broad prospects of this phosphor for LED-based applications.